Emerging Insights into the Roles of Membrane Tethers from Analysis of Whole Organisms: The Tip of an Iceberg? - Toh, Wei Hong; Gleeson, Paul A. (Frontiers in Cell and Developmental Biology, 2016)
Membrane tethers have been identified throughout different compartments of the endomembrane system. It is now well established that a number of membrane tethers mediate docking of membrane carriers in anterograde and retrograde transport and in regulating the organization of membrane compartments. Much of our information on membrane tethers have been obtained from the analysis of individual membrane tethers in cultured cells. In the future it will be important to better appreciate the network of interactions mediated by tethers and the potential co-ordination of their collective functions in vivo. There are now a number of studies which have analyzed membrane tethers in tissues and organisms which are providing new insights into the role of this class of membrane protein at the physiological level. Here we review recent advances in the understanding of the function of membrane tethers from knock outs (or knock downs) in whole organisms and from mutations in tethers associated with disease.